Bullous Pemphigoid Triggered by Thermal Burn Under Medication With a Dipeptidyl Peptidase-IV Inhibitor: A Case Report and Review of the Literature - Mai, Yosuke; Nishie, Wataru; Sato, Kazumasa; Hotta, Moeko; Izumi, Kentaro; Ito, Kei; Hosokawa, Kazuyoshi; Shimizu, Hiroshi (Frontiers in Immunology, 2018)
Bullous pemphigoid (BP) is a common autoimmune blistering disease in which autoantibodies mainly target the hemidesmosomal component BP180 (also known as type XVII collagen) in basal keratinocytes. Various triggering factors are known to induce BP onset, including radiotherapy, burns, ultraviolet exposure, surgery, and the use of dipeptidyl peptidase-IV inhibitors (DPP4i), which are widely used antihyperglycemic drugs. Here, we present a case of BP triggered by a thermal burn under the medication with DPP4i. A 60-year-old man with type II diabetes had been treated with the DPP4i linagliptin for 1 year. After the right forearm experienced a thermal burn, blisters developed around the burned area and gradually spread over the whole body with the production of autoantibodies targeting the non-NC16A domain of BP180. The diagnosis of BP was confirmed by immunohistopathological examinations. Withdrawal of linagliptin and treatment with topical steroid and minocycline achieved complete remission after 4 months. Previously, 13 cases of BP developed after thermal burns have been reported, and our case partially shared clinical features of these thermal burn-induced BP cases. Interestingly, the present case also shared typical clinical, histopathological, and immunological features of the non-inflammatory type of DPP4i-associated BP. Although the pathogeneses of thermal burn-induced BP and DPP4i-associated BP remain uncertain, the present case suggests that BP may be induced by various triggering factors.